Fluorescent ceramic, preparation method thereof, wavelength conversion device and light-emitting device
By introducing pores into fluorescent ceramics and optimizing their volume fraction and particle size, combining ceramic matrix particles and phosphor particles, the problem of temperature quenching effect of fluorescent ceramics under high lumen density laser is solved, and high light saturation threshold and light output efficiency are achieved Take into account both.
Patent Information
- Application Number
- CN202310740283.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing fluorescent ceramics have a low thermal conductivity under high lumen density lasers, which reduces the light conversion efficiency. The similar refractive index of the ceramic matrix and the phosphor particles lead to poor light output effect, making it difficult to take into account both the thermal conductivity and the light output efficiency.
The ceramic matrix particles are combined with phosphor particles. By introducing pores therein, the volume fraction and particle size of pores are optimized, and the thermal conductivity and light output efficiency of fluorescent ceramics are improved. Specific methods include preparing ceramic matrix powder, phosphor powder and pore-forming agent. mixing, calcining, presintering and sintering.
The fluorescent ceramics are achieved in taking into account both thermal conductivity and light output efficiency, improving the light saturation threshold and light output efficiency, and avoiding the occurrence of temperature quenching effect.
Smart Images

Figure CN119191873A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of light source technology, and in particular to a fluorescent ceramic and a preparation method thereof, a wavelength conversion device and a light-emitting device. Background Art
[0002] In the lighting and display industry in recent years, laser light sources have gradually become the most competitive light sources in the display industry due to their advantages such as high brightness, high resolution and lower energy consumption. In the lighting and display technology of laser-excited phosphors, the performance of the fluorescent material directly determines the quality of the obtained light source.
[0003] Generally, the fluorescent material used in laser-excited phosphor technology is mainly phosphor. At present, in the field of high-power lighting and display, the packaging material of phosphor is mainly silicone or epoxy resin and other organic resins. However, the thermal conductivity of silicone and organic resin is at a relatively low level, and silicone and resin have the disadvantage of poor thermal stability. When the laser light source radiates a high lumen density laser, the large amount of heat generated in the light conversion process cannot be quickly and effectively transferred out, causing local high temperature, resulting in a temperature quenching effect on the fluorescent material, reducing the light conversion efficiency, and making the high light saturation threshold of the fluorescent material lower.
[0004] In order to solve this problem, the main research focus of fluorescent materials is currently on how to improve the thermal conductivity of fluorescent materials to avoid the temperature quenching effect. One way is to use a ceramic matrix with high thermal conductivity and phosphor particles for encapsulation. However, if the ceramic matrix and phosphor particles are simply compounded, the light output effect of the fluorescent ceramic is poor due to the similar refractive index of the two. Therefore, the existing fluorescent ceramics cannot achieve both thermal conductivity and light output efficiency. Summary of the invention
[0005] In view of this, the purpose of the present application is to provide a fluorescent ceramic and a preparation method thereof, a wavelength conversion device and a light-emitting device, which can achieve a higher light saturation threshold and have a good light output effect.
[0006] To solve the above problems, the first technical solution provided by the present application is: a fluorescent ceramic, the fluorescent ceramic includes ceramic matrix particles, phosphor particles and pores, at least part of the pores are distributed between the ceramic matrix particles and the phosphor particles, and / or at least part of the pores are distributed between the ceramic matrix particles; and the volume percentage of the pores in the fluorescent ceramic is: 0.2m(0.3a-10b^2)+c, wherein a=(CTE1-CTE2) / CTE1, b=(n2-n1) / n1, and the value range of c is 0.05-0.2; m is the mass percentage of the phosphor particles in the fluorescent ceramic, n1 is the refractive index of the ceramic matrix particles, n2 is the refractive index of the phosphor particles, CTE1 is the thermal conductivity of the ceramic matrix particles, and CTE2 is the thermal conductivity of the phosphor particles.
[0007] Optionally, the difference in thermal conductivity between the ceramic matrix particles and the phosphor particles is greater than 20 W / (m·K).
[0008] Optionally, the refractive index difference between the ceramic matrix particles and the phosphor particles is greater than 0 and less than 0.2.
[0009] Optionally, the ceramic matrix particles are MgO particles, and the phosphor particles are garnet phosphor particles.
[0010] Optionally, the phosphor particles account for 30%-90% by mass of the phosphor ceramic.
[0011] In order to solve the above technical problems, the second technical solution provided by the present application is: a method for preparing fluorescent ceramics, which is used to prepare the above fluorescent ceramics, and the preparation method comprises:
[0012] Prepare ceramic matrix powder, phosphor powder and pore-forming agent, and mix them to obtain mixed powder;
[0013] The mixed powder is formed into a green body, the green body is calcined to remove the pore-forming agent, and pre-sintered;
[0014] The green body is sintered and annealed to obtain fluorescent ceramics.
[0015] Optionally, the pore-forming agent includes at least one of PMMA microspheres, PS microspheres, and starch.
[0016] Optionally, calcining includes keeping warm at 600-800°C for 1 to 5 hours in an air atmosphere; pre-sintering includes keeping warm at 800-1100°C for 1 to 5 hours in an air atmosphere; sintering includes keeping warm at 1500-1800°C for 1 to 10 hours under vacuum conditions; and annealing includes keeping warm at 1000-1300°C for 1 to 20 hours.
[0017] In order to solve the above technical problems, the third technical solution provided in the present application is: a wavelength conversion device, comprising the above fluorescent ceramic.
[0018] In order to solve the above technical problems, the fourth technical solution provided in the present application is: a light-emitting device, comprising an excitation light source and the above-mentioned wavelength conversion device.
[0019] The beneficial effects of the present application are as follows: the fluorescent ceramic of the present application optimizes the volume fraction of pores in the fluorescent ceramic based on the thermal conductivity and refractive index of the ceramic matrix particles and the phosphor particles, so that the high thermal conductivity of the ceramic matrix particles will not be significantly reduced due to the introduced pores, and by introducing pores with a suitable volume fraction, the light extraction efficiency of the fluorescent ceramic can be effectively improved, thereby achieving the performance of the fluorescent ceramic in both thermal conductivity and light extraction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 It is a schematic structural diagram of an embodiment of the fluorescent ceramic provided in the present application. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present application, but are not intended to limit the scope of the present application. Similarly, the following examples are only some embodiments of the present application rather than all embodiments, and all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.
[0023] Reference to "embodiment" in this application means that a particular feature, structure or characteristic described in conjunction with the embodiment may be included in at least one embodiment of this application. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.
[0024] The present application first proposes a fluorescent ceramic 10, comprising a ceramic matrix particle 11, phosphor particles 12 and pores 13. The phosphor particles 12 and the pores 13 are distributed in the ceramic matrix particle 11. Some of the pores 13 in the fluorescent ceramic 10 may be distributed between the ceramic matrix particles 11 and the phosphor particles 12, and some of the pores 13 may also be distributed between the ceramic matrix particles 11. The pores 13 of the present application have a refractive index different from that of the ceramic matrix particles 11 or the phosphor particles 12. Therefore, when the fluorescent ceramic 10 is excited to emit light by using excitation light, the excitation light incident into the fluorescent ceramic 10 changes the propagation direction of the excitation light due to the difference in refractive index when passing through the interface between the pores 13 and the ceramic matrix particles 11, or passing through the interface between the pores 13 and the phosphor particles 12. Therefore, the scattering effect in the fluorescent ceramic 10 can be increased to improve the light extraction efficiency.
[0025] In one embodiment, the phosphor particles 12 are garnet phosphor particles, such as at least one of yttrium aluminum garnet phosphor particles (YAG), lutetium aluminum garnet phosphor particles (LuAG), etc., and specifically can be YAG:Ce 3+ 、LuAG:Ce 3 + Of course, the type of phosphor particles 12 used in the phosphor ceramic 10 of the present application is not limited thereto, and other types of phosphor particles besides garnet phosphor particles may also be applicable.
[0026] In one embodiment, the mass percentage of the phosphor particles 12 in the fluorescent ceramic 10 is 30%-90%, for example, specifically 32%, 35%, 40%, 42%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 82%, 85%, 89%, etc. Based on the consideration of improving the luminous performance, the proportion of the phosphor particles 12 should not be too small, preferably not less than 30%, and the proportion of the phosphor particles 12 should be as large as possible. However, since the proportion of the phosphor particles 12 is larger, the heat generated by the fluorescent ceramic 10 is more, and the thermal conductivity of the phosphor particles 12 is relatively poor, in order to improve the luminous efficiency and reduce thermal quenching, it is necessary to introduce ceramic matrix particles 11 with better thermal conductivity as a heat conducting medium.
[0027] In one embodiment, the average particle size (D50) of the phosphor particles 12 is 1 to 30 μm. In one embodiment, it can be further 5 to 30 μm, and further 15 to 25 μm. The phosphor particles 12 of the present application can be prefabricated large-particle phosphors, such as 15 to 25 μm, and do not participate in the material transfer during the sintering process during the formation of the fluorescent ceramic, that is, the phosphor particles 12 do not participate in the sintering process of the fluorescent ceramic, so that the luminous properties of the phosphor particles 12 before and after sintering can be basically maintained, avoiding degradation during the formation of the fluorescent ceramic. In another embodiment, the average particle size (D50) of the phosphor particles 12 can be 1 to 10 μm, and further 2 to 5 μm. At this time, the phosphor particles 12 of the present application can be synthesized phosphor particles using an in-situ synthesis method during the sintering of the fluorescent ceramic. Compared with the use of prefabricated phosphors, the number of phosphor particles is greater and the dispersion is better, which is conducive to color uniformity and improving light scattering performance.
[0028] In one embodiment, the ceramic matrix particles 11 may be MgO particles. MgO particles have a high thermal conductivity, and the thermal conductivity at 25°C is about 36W / (m·K). When forming a complex phase fluorescent ceramic with the phosphor particles, it can well transfer the heat generated by the phosphor particles, reduce or avoid fluorescence quenching, and improve the luminous efficiency of the phosphor particles. And magnesium oxide ceramics belong to the cubic crystal system, which is isotropic and can be used to prepare transparent ceramics with high transmittance. However, at the same time, the excitation light or fluorescence is easy to diffuse when propagating in the MgO particles, which is not conducive to the emission of fluorescence. Therefore, it is necessary to set pores 13 to improve the scattering performance of light to improve the light emission efficiency. Of course, the ceramic matrix particles 11 of the present application are not limited to MgO particles, and can further be other types of ceramic matrix particles, such as aluminum oxide, aluminum nitride, zinc oxide, etc. In one embodiment, the average particle size (D50) of the ceramic matrix particles 11 is 1 to 10 μm, and can further be 2 to 5 μm. The use of ceramic matrix raw materials with small particle size can improve the sintering activity and help to sinter fluorescent ceramics.
[0029] In one embodiment, the volume percentage of the pores 13 in the ceramic 10 is: 0.2m(0.3a-10b^2)+c, wherein a=(CTE1-CTE2) / CTE1, b=(n2-n1) / n1, m is the mass percentage of the phosphor particles 12 in the phosphor ceramic, n1 is the refractive index of the ceramic matrix particles 11, n2 is the refractive index of the phosphor particles 12, CTE1 is the thermal conductivity of the ceramic matrix particles 11 (W / (m·K)), and CTE2 is the thermal conductivity of the phosphor particles 12 (W / (m·K)). And wherein, the value range of c is 0.05-0.2, for example, it can be 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.15, 0.16, 0.18, 0.19, etc. For the phosphor particles 12 and the ceramic matrix particles 11 in the fluorescent ceramic 10, if the refractive indexes of the phosphor particles 12 and the ceramic matrix particles 11 are close or not much different, the fluorescence is not easy to refract at the interface between the phosphor particles 12 and the ceramic matrix particles 11, which is not conducive to the emission of fluorescence. Therefore, it is necessary to increase the pores 13 to improve the scattering performance. However, on the other hand, since the introduction of the pores 13 will cause the thermal conductivity of the ceramic matrix to decrease, too many pores 13 cannot be introduced into the fluorescent ceramic 10. For a ceramic matrix with higher thermal conductivity, the content of the pores 13 can be appropriately increased, and the more the phosphor particles 12 account for in the fluorescent ceramic, the more the volume percentage of the pores 13 should be increased in order to better emit the fluorescence generated by the excitation. According to the experiment and summary of the applicant, when the volume percentage of the pores 13 is within this ratio range, the scattering performance of the fluorescent ceramic 10 to light can be better improved to improve the light emission efficiency, and the luminous efficiency of the fluorescent ceramic 10 will not be significantly reduced due to the decrease in thermal conductivity.
[0030] In one embodiment, the particle size of the pores 13 is 0.01 μm to 10 μm, and may further be 0.01 μm to 5 μm, and may further be 0.01 μm to 1 μm. The particle size of the pores 13 cannot be too large, which is not conducive to the heat conduction of the ceramic matrix and may affect the mechanical properties of the fluorescent ceramic. Since the gas in the pores 13 has a smaller refractive index than the ceramic matrix particles 11 or the phosphor particles 12, and has a large refractive index difference, light is refracted when it is incident on the interface between the pores 13 and the ceramic matrix particles 11 or the interface between the pores 13 and the phosphor particles 12, thereby scattering the light.
[0031] In one embodiment, the difference in thermal conductivity between the ceramic matrix particles 11 and the phosphor particles 12 is greater than 20 W / (m·k), and the further difference may be greater than 21 W / (m·k), 23 W / (m·k), etc. Since the thermal conductivity of the ceramic matrix particles 11 is greater than the thermal conductivity of the phosphor particles 12, the use of a ceramic matrix with high thermal conductivity can effectively conduct the heat generated by the phosphor particles 13, thereby effectively reducing thermal quenching and improving luminous efficiency.
[0032] In one embodiment, the difference in refractive index between the ceramic matrix particles 11 and the phosphor particles 12 is greater than 0 and less than 0.2, and the further difference may be less than 0.15, 0.1, etc. The refractive index of the ceramic matrix particles 11 may be greater than or less than the refractive index of the phosphor particles 12, and the difference here is the absolute value of the refractive index difference. In order to increase scattering, the difference in refractive index between the ceramic matrix particles 11 and the phosphor particles 12 should be as large as possible, but not all ceramic matrix particles 11 have a large refractive index difference with the phosphor particles 12 while having high thermal conductivity. Therefore, especially when the ceramic matrix particles 11 have high thermal conductivity and a refractive index similar to that of the phosphor particles 12, it is more necessary to control the volume fraction of the pores 13.
[0033] The present application further proposes a method for preparing a fluorescent ceramic, which is used to prepare the above-mentioned fluorescent ceramic, and the preparation method comprises the following steps:
[0034] Prepare ceramic matrix powder, phosphor powder and pore former, and mix to obtain a mixed powder. Specifically, the ceramic matrix powder, phosphor powder and pore former are weighed according to the chemical measurement, and the ceramic matrix powder, phosphor powder, pore former and auxiliary agent are ball-milled, dried and sieved to obtain a mixed powder. Among them, the pore former may include at least one of polymethyl methacrylate (PMMA) microspheres, polystyrene (PS) microspheres and starch. Of course, the present application is not limited to this, and other suitable pore formers may be used. The auxiliary agent may include an adhesive, a sintering aid and a solvent. Specifically, the adhesive is PVB, and its content is 2-5% of the total weight of the powder; the sintering aid is TEOS, and its content is 0.2-0.5% of the total weight of the powder; the solvent is anhydrous ethanol, and its amount is preferably to completely disperse the above raw materials, which is not specifically limited here. The ball milling time can be 8-24 hours. After the slurry is evenly mixed, pour it out and place it in a drying oven for drying. The evenly mixed dry powder is sieved to obtain a mixed powder. In addition, the phosphor powder may include commercial or pre-prepared phosphor powder, or phosphor precursor powder may be used. When the phosphor precursor powder is used, the corresponding raw materials may be weighed according to the composition of the phosphor, and then ball milled, granulated, calcined, crushed and sieved to obtain the desired phosphor precursor powder.
[0035] The mixed powder is formed into a green body, the green body is calcined to remove the pore-forming agent, and pre-sintering is performed. Specifically, the mixed powder is placed in a mold and first uniaxially pressed at 10-30 MPa to form a green body, and then cold isostatically pressed at 100-300 MPa to obtain a green body, and then calcined at 600-800°C in an air atmosphere for 1-5 hours to remove the pore-forming agent, and then continued to heat up to 800-1100°C in an air atmosphere for 1-5 hours to perform pre-sintering.
[0036] The green body is sintered and annealed to obtain fluorescent ceramics. Specifically, the green body is placed in a vacuum furnace and heated to 1500-1800°C under vacuum conditions and sintered for 1-10 hours to obtain porous fluorescent ceramics. Subsequently, the green body is annealed at 1000-1300°C in an air atmosphere for 1-20 hours to remove impurities and oxygen vacancies, etc., to obtain fluorescent ceramics.
[0037] The present application further proposes a wavelength conversion device, including the above-mentioned fluorescent ceramic 10. The above-mentioned fluorescent ceramic 10 can be further cut, ground and polished to form a fluorescent ceramic sheet, which can be used alone as a wavelength conversion device. It can also be combined with a substrate or other functional layers such as a reflective layer by means of bonding, welding, etc. to form a wavelength conversion device.
[0038] The present application further proposes a light emitting device, comprising an excitation light source and the above-mentioned wavelength conversion device. The excitation light source may be an LED or LD light source, etc., and the excitation light source is used to excite the fluorescent ceramic to emit light. The light emitting device may be an LED chip, an LD chip, a lighting device (such as a car light, a stage light, a searchlight, a laser flashlight, etc.), a projection device, etc.
[0039] The present application will be further described below in conjunction with specific embodiments.
[0040] Example 1
[0041] Weigh MgO powder, YAG:Ce yellow phosphor powder and pore-forming agent PMMA microspheres, wherein MgO accounts for 60% of the total mass of the powder (MgO powder and YAG:Ce yellow phosphor powder), YAG:Ce yellow phosphor powder accounts for 40% of the total mass of the powder, and 11.2% of the total mass of the powder is added. The particle size of the MgO powder is 1 μm, the particle size of the YAG:Ce yellow phosphor powder is 20 μm, and the diameter of the PMMA microsphere is 1 μm. Put the MgO powder, YAG:Ce yellow phosphor powder, PMMA microspheres and anhydrous ethanol into a ball mill for ball milling, drying, and sieving to obtain a mixed powder. Put the mixed powder into a mold for dry pressing to obtain a green body, then heat it at 600°C for 1 hour in an air atmosphere to calcine to remove the pore-forming agent, and then continue to heat it to 800°C for 1 hour in an air atmosphere for pre-sintering. The green body is placed in a vacuum furnace and heated to 1500°C under vacuum conditions and sintered for 5 hours to obtain porous fluorescent ceramics. It is then annealed at 1000°C for 5 hours in an air atmosphere to remove impurities and oxygen vacancies to obtain fluorescent ceramics.
[0042] Example 2
[0043] Weigh MgO powder, YAG:Ce yellow phosphor powder and pore-forming agent PMMA microspheres, wherein MgO accounts for 50% of the total mass of the powder (MgO powder and YAG:Ce yellow phosphor powder), YAG:Ce yellow phosphor powder accounts for 50% of the total mass of the powder, and PMMA microspheres are added at 11.5% of the total mass of the powder, wherein the particle size of the MgO powder is 5 μm, the particle size of the YAG:Ce yellow phosphor powder is 10 μm, and the diameter of the PMMA microspheres is 1 μm. Put MgO powder, YAG:Ce yellow phosphor powder, PMMA microspheres and anhydrous ethanol into a ball mill for ball milling, drying, and sieving to obtain a mixed powder. Put the mixed powder into a mold for dry pressing to obtain a green body, then heat it at 700°C for 2 hours in an air atmosphere to calcine to remove the pore-forming agent, and then continue to heat it to 1000°C for 2 hours in an air atmosphere for pre-sintering. The green body is placed in a vacuum furnace and heated to 1600°C under vacuum conditions and sintered for 5 hours to obtain porous fluorescent ceramics. It is then annealed at 1100°C for 10 hours in an air atmosphere to remove impurities and oxygen vacancies to obtain fluorescent ceramics.
[0044] Example 3
[0045] Weigh MgO powder, YAG:Ce yellow phosphor powder and pore-forming agent PMMA microspheres, wherein MgO accounts for 10% of the total mass of the powder (MgO powder and YAG:Ce yellow phosphor powder), YAG:Ce yellow phosphor powder accounts for 90% of the total mass of the powder, and 12.7% of the total mass of the powder is added. The particle size of the MgO powder is 10 μm, the particle size of the YAG:Ce yellow phosphor powder is 5 μm, and the diameter of the PMMA microsphere is 1 μm. Put the MgO powder, YAG:Ce yellow phosphor powder, PMMA microspheres and anhydrous ethanol into a ball mill for ball milling, drying, and sieving to obtain a mixed powder. Put the mixed powder into a mold for dry pressing to obtain a green body, then heat it at 800°C for 5 hours in an air atmosphere to calcine to remove the pore-forming agent, and then continue to heat it to 1100°C for 5 hours in an air atmosphere for pre-sintering. The green body is placed in a vacuum furnace and heated to 1800°C under vacuum conditions and sintered for 10 hours to obtain porous fluorescent ceramics. It is then annealed at 1300°C for 20 hours in an air atmosphere to remove impurities and oxygen vacancies to obtain fluorescent ceramics.
[0046] Example 4
[0047] Weigh MgO powder, LuAG:Ce green phosphor powder and pore-forming agent PMMA microspheres, wherein MgO accounts for 60% of the total mass of the powder (MgO powder and LuAG:Ce green phosphor powder), YAG:Ce yellow phosphor powder accounts for 40% of the total mass of the powder, and 11.6% of the total mass of the powder is added. The particle size of the MgO powder is 1 μm, the particle size of the LuAG:Ce green phosphor powder is 20 μm, and the diameter of the PMMA microsphere is 1 μm. Put the MgO powder, LuAG:Ce green phosphor powder, PMMA microspheres and anhydrous ethanol into a ball mill for ball milling, drying, and sieving to obtain a mixed powder. Put the mixed powder into a mold for dry pressing to obtain a green body, then heat it at 600°C for 1 hour in an air atmosphere to calcine to remove the pore-forming agent, and then continue to heat it to 800°C for 1 hour in an air atmosphere for pre-sintering. The green body is placed in a vacuum furnace and heated to 1500°C under vacuum conditions and sintered for 1 hour to obtain porous fluorescent ceramics. It is then annealed at 1000°C for 5 hours in an air atmosphere to remove impurities and oxygen vacancies to obtain fluorescent ceramics.
[0048] It should be noted that the various optional implementations introduced in the embodiments of the present application can be implemented in combination with each other or can be implemented separately, and the embodiments of the present application are not limited to this.
[0049] In the description of the present application, it should be understood that the terms "upper", "lower", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, and a specific orientation structure and operation. Therefore, it cannot be understood as a limitation on the present application. In addition, "first" and "second" are only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present application, unless otherwise specified, "multiple" means two or more.
[0050] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0051] The above embodiments are described with reference to the accompanying drawings, and other different forms and embodiments are also feasible without departing from the principles of the present application, so the present application should not be constructed as a limitation of the embodiments proposed herein. More specifically, these embodiments are provided so that the present application will be perfect and complete, and the scope of the present application will be conveyed to those skilled in the art. In the accompanying drawings, the component sizes and relative sizes may be exaggerated for clarity. The terms used herein are only based on the purpose of describing specific embodiments and are not intended to be limiting. The terms "comprising" and / or "including" when used in this specification indicate the presence of the features, integers, components and / or components, but do not exclude the presence or increase of one or more other feature integers, components, components and / or their groups. Unless otherwise indicated, when stated, the numerical range includes the upper and lower limits of the range and any sub-ranges therebetween.
[0052] The above descriptions are only some embodiments of the present application, and do not limit the protection scope of the present application. Any equivalent device or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A fluorescent ceramic, characterized in that: The fluorescent ceramic comprises ceramic matrix particles, phosphor particles and pores, at least part of the pores are distributed between the ceramic matrix particles and the phosphor particles, and / or at least part of the pores are distributed between the ceramic matrix particles; And the volume percentage of the pores in the fluorescent ceramic is: 0.2m(0.3a-10b^2)+c, wherein a=(CTE1-CTE2) / CTE1, b=(n2-n1) / n1, and the value range of c is 0.05-0.2; m is the mass percentage of the phosphor particles in the fluorescent ceramic, n1 is the refractive index of the ceramic matrix particles, n2 is the refractive index of the phosphor particles, CTE1 is the thermal conductivity of the ceramic matrix particles, and CTE2 is the thermal conductivity of the phosphor particles.
2. The fluorescent ceramic according to claim 1, characterized in that: The difference in thermal conductivity between the ceramic matrix particles and the phosphor particles is greater than 20 W / (m·k).
3. The fluorescent ceramic according to claim 1, characterized in that: The difference in refractive index between the ceramic matrix particles and the phosphor particles is greater than 0 and less than 0.
2.
4. The fluorescent ceramic according to claim 1, characterized in that: The ceramic matrix particles are MgO particles, and the phosphor particles are garnet phosphor particles.
5. The fluorescent ceramic according to claim 1, characterized in that: The mass percentage of the phosphor particles in the fluorescent ceramic is 30%-90%.
6. A method for preparing fluorescent ceramics, characterized in that: The preparation method is used to prepare the fluorescent ceramics according to claims 1 to 5, and the preparation method comprises: Prepare ceramic matrix powder, phosphor powder and pore-forming agent, and mix them to obtain mixed powder; forming the mixed powder into a green body, calcining the green body to remove the pore-forming agent, and pre-sintering; The green body is sintered and annealed to obtain the fluorescent ceramic.
7. The preparation method according to claim 6, characterized in that: The pore-forming agent includes at least one of PMMA microspheres, PS microspheres and starch.
8. The preparation method according to claim 6, characterized in that: The calcination includes keeping the temperature at 600-800°C for 1-5 hours in an air atmosphere; the pre-sintering includes keeping the temperature at 800-1100°C for 1-5 hours in an air atmosphere; the sintering includes keeping the temperature at 1500-1800°C for 1-10 hours under vacuum conditions; and the annealing includes keeping the temperature at 1000-1300°C for 1-20 hours.
9. A wavelength conversion device, characterized in that: The wavelength conversion device comprises the fluorescent ceramic according to claims 1-5.
10. A light emitting device, characterized in that: The light emitting device comprises an excitation light source and the wavelength conversion device according to claim 9.
